The Effect of Using NLP Techniques on Writing Ability of EFL Learners - Elham ZARFSAZ; SALAMAT, Marjan (LPPM Universitas Advent Indonesia, 2024)
Neuro-Linguistic Programming (NLP) has the potential to help language learners; however, it has received scant attention. Collingwood (2001), NLP is a technique to investigate the relationship between how our mind works (Neuro) , how we communicant verbally and nonverbally (linguistic), and our patterns of behavior and feeling(program). The present study was an attempt to investigate the effect of NLP techniques on the writing ability of English as a Foreign Language. To achieve this goal, two intact classes of students were selected to form an experimental group (n=15) and a control group (n=15). A writing ability pretest (based on the course content) was given to all participants. The participants in the experimental group were familiarized with NLP techniques to be able to implement these techniques in their writing. In the control group, the conventional approach to teach was used. Comparing the results the posttest results through ANCOVA, it was found that implementation of NLP techniques can have significant effect on writing ability EFL learners. Therefore, NLP can improve writing ability by improving various processes such as communication and information processing. It can be used by teachers, trainers and syllabus design.